The Role of Heterotrophic Bacteria and Archaea in the Transformation of Lignin in the Open Ocean - McDonald, Natasha; Achterberg, Eric P.; Carlson, Craig A.; Gledhill, Martha; Liu, Shuting; Matheson-Barker, Julia R.; Nelson, Norm B.; Parsons, Rachel J. (Frontiers in Marine Science, 2019)
Abstract The pelagic ocean receives terrigenous inputs of a range of organic compounds; however, the role that this terrigenous material plays in the ocean carbon cycle and biological pump is not entirely understood, and questions remain as to how oceanic cycles of terrigenous and autochthonous carbon interact. A significant portion of organic carbon that cannot be utilized by marine microbes in the epipelagic ocean escapes microbial remineralization to be sequestered in the deep ocean as refractory dissolved organic matter. Lignin, a ‘model’ terrigenous compound, is thought to be refractory in the open ocean unless chemically altered. However, in this study, incubation experiments performed using lignin-amended oligotrophic seawater from the Sargasso Sea exhibited bacteria and archaea growth that doubled compared to unamended control treatments. The increase in bacteria and archaea cell abundance in lignin-amended treatments coincided with a 21-25% decrease in absorbance (250 – 400 nm) of chromophoric dissolved organic matter (CDOM), suggesting that certain microbes may be capable of altering fractions of this ostensibly recalcitrant organic matter. Furthermore, the microbial response to the lignin-amended treatments appears to be taxon-specific. Two phyla of Archaea, Euryarchaeota and Thaumarchaeota, exhibited an increase in abundance of 7 fold and 28 fold (from 2.42 x 106 cells L-1 to 1.72 x 107 cells L-1, and from 1.60 x 106 cells L-1 to 4.54 x 107 cells L-1, respectively), over four days of incubation in lignin-amended treatments. Additionally, an increase of 11 fold and 13 fold, (from 2.93 x 106 cells L-1 to 3.30 x 107 cells L-1, and from 3.26 x 106 cells L-1 to 4.28 x 107 cells L-1, respectively) was observed in the abundance of these phyla in treatments containing lignin with added nitrogen and phosphorus, thus raising questions regarding primary and / or secondary responses to lignin degradation. Our findings indicate that marine bacteria and archaea play a role in the transformation of the optical properties of lignin in the open ocean and that they may serve as a potential sink for a portion of the lignin macromolecule.